Association between serum ferritin and hemoglobin levels and bone health in Korean adolescents: A nationwide population-based study. Issue 51 (December 2017) - Jung, Dong-Wook; Park, Joo-Hyun; Kim, Do-Hoon; Choi, Moonyoung; Kim, Shinhye; Kim, Hyonchong; Seul, Da-eun; Park, Soo Gyeong; Jung, Jin-Hyung; Han, Kyungdo; Park, Young-Gyu
Abstract : Abstract: It is important to identify risk factors for low bone mass at a young age. An influence of iron store on bone health in the general population has been reported but has not been studied in adolescents. This study aimed to investigate the relationship between hemoglobin and serum ferritin levels and bone mineral content (BMC) in South Korean adolescents. This study was based on data collected during the 2009to 2010 Korea National Health and Nutrition Examination Survey. We included 1321 participants aged 10 to 18 years. BMC was measured at the femur and lumbar spine using dual-energy x-ray absorptiometry, and hemoglobin and serum ferritin levels were examined. In boys, hemoglobin and serum ferritin levels were positively associated with BMC of the total femur and lumbar spine after adjusting for confounders, and hemoglobin levels significantly increased as BMC increased at all sites ( P for trend = .001 for total femur, .01 for femur neck, and <.001 for lumbar spine). Likewise, serum ferritin levels showed increasing trends according to increasing BMC of the total femur and lumbar spine in boys ( P for trend = .04 for total femur; and <.001 for lumbar spine). However, these associations were not observed in girls. This study suggests a positive relationship between serum ferritin and hemoglobin levels and BMC in South Korean adolescent boys. Abstract : Supplemental Digital Content is available in the text